ANALISIS PEWARNA BUATAN PADA SELAI ROTI YANG BERMEREK DAN TIDAK BERMEREK YANG BEREDAR DI KOTA MEDAN TAHUN 2013 - Arini Agustina; irnawati marsaulina; TaufIK Ashar (Lingkungan dan Kesehatan Kerja, 2014)
Analysis of Artifical Dyes Rate on The Jam Branded Bread and Jam Unbranded Jam Bread on Medan City for 2013. Jam bread is a popular product of snack to eat with variously types, have a prominenly colors, that many people like it. In order to attract the consumer mostly product may cause a dangerous impact over the human health. To view whether the uses of the artificial dyes on jam bread fulfilling the requirement for health.The method used study in survey research with descriptive one. The sampel taken from Central Market , Simpang Limun Market, Indomaret in Sakti Lubis Road and Carrefour in Plaza Medan Fair at Medan City, bring it to Provincial Health Laboratory in North Sumatra for examination.The result showed that from 6 samples of jam bread branded and in examination found that 4 samples contained artifical dyes as permitted that is Amaranth and Tartrazine, and another 6 samples of jam bread non-branded in examination, 3 samples containing artificial dyes as permitted that Amaranth and Tartrazine. The rate noted on 6 samples of jam branded bread found at least 2 samples not fulfilling the requirement that is 346 mg/kg, 205 mg/kg and 1 sample of jam non-branded bread not fulfilling the requirement that is 295 mg/kg.It is suggested to Balai POM is seriously to make a strictly control and supervision into the uses of additional substances for producing foods. Keywords : Jam bread, snack, prominenly colors, artificial dyes, the rate.